2015
DOI: 10.3791/52557
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Testing of Plant Seed Meal-based Wood Adhesives

Abstract: Recently, the interest in plant seed meal-based products as wood adhesives has steadily increased, as these plant raw materials are considered renewable and environment-friendly. These natural products may serve as alternatives to petroleum-based adhesives to ease environmental and sustainability concerns. This work demonstrates the preparation and testing of the plant seed-based wood adhesives using cottonseed and soy meal as raw materials. In addition to untreated meals, water washed meals and protein isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Soy meal was obtained from Kentwood Co-op (Kentwood, LA, USA). The working soy meal was obtained by grinding the meal in a cyclone sample mill (Model 3010–014, UDY Corporation, Fort Collins, CO, USA) to pass a 0.5-mm steel screen [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Soy meal was obtained from Kentwood Co-op (Kentwood, LA, USA). The working soy meal was obtained by grinding the meal in a cyclone sample mill (Model 3010–014, UDY Corporation, Fort Collins, CO, USA) to pass a 0.5-mm steel screen [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…). With this trend, our group has demonstrated that cottonseed meal (CSM)‐based products can be used as wood adhesives . Whereas untreated CSM‐based adhesives showed poor water resistance, water‐washed cottonseed meal (WCSM) and cottonseed protein isolate (CSPI) possess much better water resistance, even better than the more widely studied soy protein isolate (SPI)‐based adhesives …”
Section: Introductionmentioning
confidence: 99%
“…While most of the testing parameters were set as per the protocols for preparation and testing of plant seed meal-based wood adhesives reported previously, some parameters on post-bonding conditioning and treatments were adopted from European standards EN204 and EN14257 [ 27 , 28 ]. Adhesive slurries were prepared by mixing and stirring WCSM with appropriate deionized water to a solid content of 11% for 1 h at room temperature (22–23 °C).…”
Section: Methodsmentioning
confidence: 99%